Leisure-Time Physical Activity in People with Advanced Cancer: Exploring the Perspectives of Adults Diagnosed with Stage 4 Cancer and of Oncology Physiotherapists in Canada - Shallwani, Shirin Mehdi (Université d'Ottawa / University of Ottawa, 2022)
Background: Despite improving survival rates, people with advanced cancer experience high symptom burden, functional challenges, and negative impacts upon their quality of life. Moreover, these individuals frequently report unfulfilled needs related to supportive care, including rehabilitation support. Leisure-time physical activity (LPA), including exercise, has been found to be beneficial for people following diagnosis of cancer. However, little is known about LPA for individuals living with advanced cancer, particularly from a rehabilitation perspective. Purpose and objectives: The overall purpose of my dissertation research is to explore LPA in people with advanced cancer, through the perspectives of adults diagnosed with stage 4 cancer as well as those of oncology physiotherapists. Specific objectives are: (1) to map the research and understand key concepts from the literature about LPA in individuals with advanced cancer; (2) to explore the perspectives and experiences of LPA in adults diagnosed with stage 4 cancer; and (3) to describe the clinical practices, knowledge, skills, and perspectives of oncology physiotherapists related to LPA in the advanced cancer population. Methods: To meet these objectives, I conducted three research studies: (1) a scoping review of 92 articles exploring LPA in people with advanced cancer; (2) a qualitative interpretive-description study, involving individual, semi-structured interviews with 20 Canadian adults diagnosed with stage 4 cancer; and (3) a mixed-methods study, consisting of an online survey with 62 Canadian oncology physiotherapists, followed by qualitative, individual interviews with 13 physiotherapists. Results: The scoping review demonstrated a recent surge in research on the topic of LPA in advanced cancer, with many studies adopting quantitative methods and investigating aerobic and resistance exercise interventions. These studies have contributed to important research developments highlighting the safety, feasibility, and benefits of such interventions for people with advanced cancer. This scoping review also identified several gaps in the literature, particularly highlighted by the few qualitative studies exploring patient perspectives and experiences with different types of LPA. The second study helped address some of the research gaps noted in the scoping review. In this qualitative interpretive-description study, individuals with stage 4 cancer revealed the diverse and fluid nature of their experiences with LPA, necessitating intentional planning and modifications of activities. Moreover, important health benefits and psychosocial meanings of activity participation were identified. In addition, common supportive care needs related to LPA were recognized through this work. In particular, the participants desired professional LPA support that is integrated, interprofessional, accessible, and tailored to their individual abilities and preferences. To complement the patient perspectives and experiences, the third study offered insight on the perspectives of rehabilitation professionals. This mixed-methods study with oncology physiotherapists demonstrated positive views about the safety, importance, and benefits of activity in people with advanced cancer. Key considerations with this population included addressing cancer-related issues (e.g., bone metastases), identifying individually meaningful goals, and tailoring activity recommendations. The physiotherapists also highlighted their overall roles in optimizing functional capacity and alleviating symptom burden in people with advanced cancer. The lack of awareness about the role of physiotherapy and the limited access to rehabilitation services in oncology were identified as important challenges. Conclusions: The overall findings from this dissertation research highlight the scope of literature on LPA in advanced cancer and offer patient and professional perspectives related to this topic. As such, these findings may help inform the design and integration of supportive care resources targeted to this population. Strategies to promote LPA in this population require consideration of the complexities associated with advanced cancer and the important meanings of LPA for people living with this challenging diagnosis. Physiotherapists can be well-suited to promote safe, meaningful LPA in the advanced cancer population, as well as to optimize functional activity and symptom management. Practically, these findings support a patient-centered approach to encourage appropriate LPA in the care of people with advanced cancer. Key elements include: (1) comprehensive, regular patient assessment; (2) open communication with patients and families; (3) interprofessional collaboration between oncology care providers and specialized rehabilitation professionals; (4) integrated, routine delivery of LPA information and individualized activity recommendations; and (5) access to tailored LPA resources and programs within cancer care and community-based settings. Additional research is warranted to examine different types of LPA and explore other rehabilitation needs, particularly in understudied subgroups of advanced cancer (e.g., non-breast cancer). Moreover, further efforts are needed to develop, evaluate, and implement clinical strategies targeting LPA within integrated care models for advanced cancer. Simultaneously, educational initiatives are necessary to enhance relevant knowledge in physiotherapists and oncology care providers. These can support the personalization of LPA resources, facilitate interprofessional collaboration, and improve the quality and integration of rehabilitation services in cancer care. Therefore, the findings of my dissertation research provide comprehensive and applicable knowledge about diverse patient and professional perspectives related to LPA in the advanced cancer population. This work can support future efforts aimed at facilitating LPA participation and enhancing supportive care experiences in individuals living with advanced cancer.
Keywords: advanced cancer; oncology; physical activity; leisure activity; physiotherapy; rehabilitation